Derived Adjectives in English Sentences: A Morphosyntactic Study of Cecelia Ahern’s Novel The Time of My Life - Putu Devi Maharani Maharani; Komang Dian Puspita Chandra; Ni Komang Sri Budari Dana Putri (Journal of linguistics, culture and communication, 2025)
This study investigates the intersection between morphology and syntax, known as morphosyntax, focusing on the formation and syntactic roles of derived adjectives in the novel The Time of My Life. The objectives of this research are to identify the morphological types of derived adjectives and to analyze their syntactic functions within sentence structures. The study employs the theories proposed by Quirk et al. (1985), Plag (2002), and Brown & Miller (1994) as the analytical framework. The data were collected through a library research method and analyzed qualitatively using both formal and informal descriptive techniques. The findings reveal that thirteen suffixes are used to form derived adjectives in the novel, namely –ful, –able, –ish, –ous, –al, –ic, –less, –y, –ive, –ly, –ing, –ed, and –ary. These suffixes contribute to the creation of adjectives that serve three main syntactic functions, such are predicative, attributive, and postpositive. The study highlights the dynamic relationship between morphological processes and syntactic distribution, illustrating how derivational morphology contributes to syntactic variation in English literary texts.